2023
DOI: 10.1055/s-0043-1769101
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Revascularizing the Left Subclavian Artery via Carotid-Subclavian Bypass

Bartosz Rylski,
Monika Matzdorf,
Stoyan Kondov
et al.

Abstract: Background Endovascular thoracic aortic treatment frequently requires extending the proximal landing zone up into the aortic arch with consecutive covering of the left subclavian artery orifice. Our aim was to report on our outcome of left subclavian artery revascularization using carotid-subclavian bypass via lateral access to the subclavian artery. Methods Patients' charts in our aortic center were screened for all those who had undergone carotid-subclavian bypass during endovascular thoracic aorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Recent meta-analyses demonstrated that revascularization of the LSA is associated with decreased risks of cerebrovascular accidents, spinal cord ischemia (SCI), and left upper limb ischemia but at the cost of worrying local complications [ 3 , 4 , 5 ]. Different alternative endovascular solutions, such as the parallel grafts techniques, customized fenestrated or scalloped or branched endograft, have been designed to challenge left carotid-LSA bypass or transposition [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Among total endovascular solutions, the former are versatile but have inconsistent durability, while the latter offer encouraging results but are complex procedures and require long manufacturing time.…”
Section: Introductionmentioning
confidence: 99%
“…Recent meta-analyses demonstrated that revascularization of the LSA is associated with decreased risks of cerebrovascular accidents, spinal cord ischemia (SCI), and left upper limb ischemia but at the cost of worrying local complications [ 3 , 4 , 5 ]. Different alternative endovascular solutions, such as the parallel grafts techniques, customized fenestrated or scalloped or branched endograft, have been designed to challenge left carotid-LSA bypass or transposition [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Among total endovascular solutions, the former are versatile but have inconsistent durability, while the latter offer encouraging results but are complex procedures and require long manufacturing time.…”
Section: Introductionmentioning
confidence: 99%